Cambridge handbook of culture, organizations, and work - Bhagat, Rabi S. , 1950-; Steers, Richard M. (Cambridge University Press, 2009)
With contributions from an international team of scholars, this book reviews, analyses, and integrates available theory and research to give the best information possible concerning the role of culture and cultural differences in organizational dynamics.